Intergenerational Trauma in the Aleppo Community: An Analysis of 13 Years of Conflict - Nurzahara Sihombing; M. Agung Rahmadi; Fairuz Azzahra; Sila Tsabita Zahra; Nafiza Fadhilatul Ulya Damanik; Helsa Nasution; Luthfiah Mawar; Winda Yulia Gitania Br Sembiring (Jurnal Ventilator, 2026)
This meta-analysis provides an in-depth evaluation of the dynamics of intergenerational trauma within the Aleppo community over 13 years of armed conflict (2011–2024) through a systematic synthesis of 47 empirical studies involving 12,873 cross-generational participants. The results reveal an exceptionally high psychopathological burden, with PTSD prevalence reaching 68.4% (95% CI = 65.2–71.6) in the first generation and 42.3% (95% CI = 39.1–45.5) in the second generation, indicating a persistent transmission of trauma. Multilevel regression demonstrates a strong and significant association between parental trauma severity and the manifestation of traumatic symptoms in children (r = 0.62, p < .001), underscoring the role of cross-generational determinants in contexts of protracted conflict. Major depressive disorder is identified in 55.7% of parents and 37.2% of children, while anxiety prevalence reaches 61.3% in the first generation and 44.8% in the second generation. Structural equation modeling reveals three principal pathways of trauma transmission, namely maladaptive parenting patterns dysfunctional family communication, and anxiety modeling processes. These findings extend beyond the analyses of Amping et al. (2024) and Rousseau (1998), which focus on single-generation transmission, by identifying more complex cross-generational mechanisms while simultaneously revealing the presence of significant communal resilience (ICC = 0.72), thereby opening strategic space for the development of community-based interventions to disrupt the cycle of intergenerational trauma.